Experimental study on cracking behavior of steel fiber-reinforced concrete beams with BFRP bars under repeated loading. (1st July 2021) - Li, Zongze; Zhu, Haitang; Du, Chengxiang; Gao, Danying; Yuan, Jiansong; Wen, Chengcheng
Highlights: The flexural performance and cracking behavior of steel fiber-reinforced concrete (SFRC) beams with BFRP bars under repeated loading were investigated. The cracking moment, crack spacing, and crack width of SFRC beams with BFRP bars were assessed. The effects of the concrete strength, BFRP reinforcement ratio, steel fiber volume ratio, and steel fiber shape on the flexural performance and cracking behavior were evaluated. A new theoretical calculation model for the cracking moment, crack spacing, and crack width of SFRC beams with BFRP bars is proposed. Abstract: This study aimed to investigate the feasibility of using steel fibers to control crack spacing and width for concrete beams reinforced with basalt fiber-reinforced polymer (BFRP) bars under repeated loading. Four-point bending tests were performed on 11 concrete beams reinforced with BFRP bars having various concrete strength grades, BFRP reinforcement ratios, steel fiber volume ratios, and steel fiber shapes. The flexural strength, cracking moment, crack propagation, crack spacing, and crack width of the beams were obtained from experiment, among which the cracking moment, crack spacing, and crack width were compared with their counterpart predicted from analytical models in various codes and literature. Compared with concrete beams reinforced with BFRP bars but without steel fibers, steel fiber-reinforced concrete (SFRC) beams with BFRP bars exhibited a higher cracking resistance, higher cracking moment and flexural strength, and smaller crack spacing and width. The use of high-strength concrete increased cracking moment and reduced crack width and spacing; however, the BFRP reinforcement ratio only affected crack width and spacing but does not affect cracking moment. The ACI 400.1R-15, CAS S806-12, and Chinese national standard GB 50608-2010 codes all underestimated the cracking moment of SFRC beams with BFRP bars but overestimated the crack width. Finally, a series of new analytical models based on the tensile constitutive law of SFRC were developed for the cracking moment, crack spacing, and crack width and validated by experimental results that they performed better than their counterparts in ACI 400.1R-15 and CAS S806-12 codes.